ANALIS PERAN Q-RIS DALAM MENIGKATKAN KUALITAS LAPORAN PENJUALAN PADA UMKM - Aulia Rizky Lubis; Muhammad Irwan Padli Nasution (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This study aims to analyze the role of the Quick Response Code Indonesian Standard (QRIS) in improving the quality of sales reports among Micro, Small, and Medium Enterprises (MSMEs). The development of digital payment systems encourages MSMEs to adapt to non-cash transaction methods that are faster, safer, and more efficient. QRIS functions not only as a digital payment instrument but also as an automatic transaction recording system that supports the preparation of more accurate and well-structured sales reports. The research method employed is descriptive qualitative with a field study approach, conducted through observations of QRIS implementation in MSME sales activities. The results indicate that the use of QRIS contributes positively to improving the accuracy, orderliness, and transparency of sales reports. Digitally recorded transaction data facilitates MSME actors in monitoring revenue and periodically evaluating business performance. In addition, the implementation of QRIS promotes business professionalism and enhances consumer trust. Nevertheless, the optimal utilization of QRIS still faces challenges, particularly limited digital literacy and the underutilization of transaction data. Therefore, continuous education is required so that the benefits of QRIS can be optimally realized by MSMEs.